Neutron transfer in reaction 18O + 181Ta with formation of neutron-rich oxygen isotopes. (May 2020) - Penionzhkevich, Yu E; Lukyanov, S M; Azhibekov, A K; Naumenko, M A; Issatayev, T; Kolesov, I V; Maslov, V A; Mendibayev, K; Zernyshkin, V A; Kuterbekov, K A; Mukhambetzhan, A M
Abstract: Differential cross sections for the formation of oxygen isotopes in the reaction 18 O + 181 Ta have been measured at projectile nucleus energy 10 A ⋅MeV on the high-resolution magnetic spectrometer MAVR. Theoretical analysis of product yields has been performed in the finite-range distorted-wave Born approximation formalism using the FRESCO code under the assumption of sequential neutron transfer mechanism. The results of calculations are in good agreement with experimental data.